THERMAL DEGRADATION BEHAVIOR OF RICE HUSK THROUGH CATALYTIC GASIFICATION FOR SYNGAS PRODUCTION - ADRIAN , LOY CHUN MINH (2019)
Energy crises and environmental issues associated with fossil fuels have urged for alternative, sustainable and renewable energy. Syngas is an attractive renewable energy in future energy generation since it is a clean fuel